Public health emergency operation centres: status, gaps and areas for improvement in the Eastern Mediterranean Region. (28th June 2022) - Elmahal, Osman M; Abdullah, Ali; Elzalabany, Manal K; Anan, Huda Haidar; Samhouri, Dalia; Brennan, Richard John
Abstract : The functionality of Public Health Emergency Operations Centres (PHEOCs) in countries is vital to their response capacity. The article assesses the status of National PHEOCs in the 22 countries of the Eastern Mediterranean Region. We designed and administered an online survey between May and June 2021. Meetings and Key Informant Interviews were also conducted with the emergency focal points in the WHO country offices and with other select partners. We also collected data on PHEOCs from the Joint External Evaluations conducted in the Region between 2016 and 2018 in 18 countries, and intra-action review mission reports conducted in 11 countries to review the response to COVID-19 during May 2020–June 2021 - and other relevant mission reports. Only 12 countries reported having PHEOC with varying levels of functionality and 10 of them reported using PHEOC for their response operations. This review formed the baseline of capacity requirements of National PHEOC in each country and will facilitate identifying benchmarks of areas of improvement for future national, WHO and partners support.